2016
DOI: 10.1158/1940-6207.capr-15-0311
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled, Phase II, Presurgical Biomarker Trial of Celecoxib Versus Exemestane in Postmenopausal Breast Cancer Patients

Abstract: In breast cancer presurgical trials, the Ki-67 labeling index predicts disease outcome and offers clues to the preventive potential of drugs. We conducted a placebo-controlled trial to evaluate the activity of exemestane and celecoxib before surgery. The main endpoint was the change in Ki-67. Secondary endpoints were the modulation of circulating biomarkers. Postmenopausal women with histologically confirmed estrogen receptor-positive breast cancer were randomly assigned to exemestane 25 mg/day (n ¼ 50), or ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
1
9
1
Order By: Relevance
“…reported a trend towards lower Ki67 after neoadjuvant treatment with the selective COX‐2 inhibitor celecoxib . However, a recent neoadjuvant randomized controlled phase II trial of celecoxib versus exemestane did not show any antiproliferative effect of celecoxib . In this study, there was no statistically significant difference in Ki67 among patients with and without reported preoperative NSAID use (data not shown).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…reported a trend towards lower Ki67 after neoadjuvant treatment with the selective COX‐2 inhibitor celecoxib . However, a recent neoadjuvant randomized controlled phase II trial of celecoxib versus exemestane did not show any antiproliferative effect of celecoxib . In this study, there was no statistically significant difference in Ki67 among patients with and without reported preoperative NSAID use (data not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Results from randomized trials of NSAID use in relation to prognosis in the preoperative setting have been inconsistent; some showed a decrease in tumor volume or anti‐tumor transcriptional response others did not find any effect . However, perioperative NSAID administration was shown to significantly improve short‐term prognosis .…”
mentioning
confidence: 99%
“… 126 Moreover, it was suggested that the anticancer effect of combination therapy might have mainly resulted from exemestane instead of celecoxib. 127 …”
Section: Integrating Celecoxib Into Bc Treatmentmentioning
confidence: 99%
“…Selective COX-2 inhibitors have also been explored as therapeutic or preventive agents in various oncologic settings. 13,14 Several studies have evaluated celecoxib in the neoadjuvant setting for breast cancer as a monotherapy 15,16 or combined with endocrine therapy. 17,18 In addition to toxicity and safety concerns, the benefits of such strategies to patients with breast cancer were not sufficiently high for these agents to be incorporated into standard care, and the development of COX-2 inhibitors in oncology thus fell short of initial expectations.…”
Section: Introductionmentioning
confidence: 99%